Impact of transition to identified gender on transgender adults’ quality of life, autistic traits and experiences of interpersonal interactions - Nobili, Anna (2019)
Transgender people often experience poor mental health and there is a strong clinical impression that this population reports high rates of autistic traits. These issues potentially have a negative impact upon their Quality of Life (QoL) and interpersonal issues. Transgender people generally wish to undergo Gender-Affirming Treatments (GAT), which consist of medical interventions such as Cross-Sex Hormone Treatment (CHT) and gender-affirming surgeries. These procedures help align transgender people’s physical characteristics with the gender they identify with and help improve their physical quality of life. However, there is need to understand the impact of undergoing GAT upon mental health-related QoL and social interactions. Thus, Study 1, a systematic review and meta-analysis, was conducted to explore the evidence related to different dimensions of quality of life as well as to gain understanding of the effect of CHT upon mental health-related QoL. Results of this study suggest that transgender people have poorer mental health-related quality of life than the general population. Additionally, some evidence suggests that post-treatment their disadvantage becomes less apparent.